Corrosion Considerations Related to Carbon Steel Radioactive Waste Packages Exposed to Cementitious Materials. Issue 63 (20th February 2017) - Kursten, Bruno; Druyts, Frank; Smart, Nick R.; Macdonald, Digby D.; Gens, Robert
ABSTRACT: The Supercontainer is the reference concept for the post-conditioning of vitrified high-level radioactive waste and spent fuel in Belgium. It consists of a prefabricated concrete buffer that completely surrounds a carbon steel overpack. In this highly alkaline environment (pH ∼ 13.6) and under normal conditions (i.e. without the ingress of aggressive species), the carbon steel overpack will be protected by a passive oxide film, which is believed to result in very low uniform corrosion rates. This paper gives an overview of the status of the uniform corrosion, pitting corrosion and stress corrosion cracking behaviour of carbon steel expected during the waste disposal period.